Faithful Translation Method in Translating Movie of Kung Fu Panda 1 - Syafitri, Baiq Inda Rahma; Baharuddin; Wardana, Lalu Ali (Journal of English Education Forum (JEEF), 2025)
This study examines the application of the faithful translation method in the Indonesian subtitles of the animated film Kung Fu Panda 1, focusing on the dialogues between Po and Master Shifu. Drawing on Peter Newmark’s translation theory, the analysis centers on two main aspects: the preservation of contextual meaning and the adherence to grammatical structure in the target language. A total of 262 dialogue pairs were analyzed using a qualitative content analysis approach, supported by quantitative data. The findings reveal that 124 translations (47.33%) reflect faithful translation. Despite this limitation, the faithful method demonstrated its effectiveness in preserving contextual meaning by accurately transferring cultural references, emotional nuances, and intended messages, while also maintaining grammatical integrity through appropriate subject–verb agreement, clause structure, tense consistency, and natural syntax in the target language. This research highlights the importance of balancing fidelity to the source text with the practical demands of audiovisual translation, contributing valuable insight into the use of the faithful method in subtitled films.faithful translation